412 - Empowerment for people living with dementia: an integrative literature review. (October 2021) - Van Corven, Charlotte T.M.; Bielderman, Annemiek; Wijnen, Mandy; Leontjevas, Ruslan; Lucassen, Peter LBJ; Graff, Maud JL; Gerritsen, Debby L.
Abstract : Introduction: Although the concept of empowerment seems useful for good care and support for people living with dementia, there is a lack of understanding as to how to define this concept. Therefore, insight is needed in what empowerment means for people living with dementia. Methods: We performed an integrative literature review (PubMed, CINAHL, PsychINFO), including articles that addressed empowerment for people living with dementia in their title or abstract. Using qualitative data analysis software ATLAS.ti, we applied open codes to describe all relevant aspects of included articles. Common themes and categories were identified using inductive reasoning and constant comparison. Results: Sixty-nine articles were included. We identified four themes: (1) description of the state of being empowered, (2) the process of empowerment, (3) contribution of the environment to the empowerment process, and (4) effects on other variables. We combined these results with the conceptual framework of our previous qualitative study on the definition of empowerment for people living with dementia based on stakeholders' perspectives into a revised conceptual framework. Subsequently, the combined information of both studies was visualized in a revised conceptual framework. Conclusion: This literature review provides more details as to the role of the environment for empowerment of people living with dementia and suggests that empowerment can be considered a dynamic process, taking place through interaction between the person living with dementia and their environment. Our revised conceptual framework of empowerment can serve as a basis for future studies on empowerment for people living with dementia, and to support (in)formal caregivers in the empowerment process.